0290 Associations between sleep duration and sedentary behavior in healthy, young adults. (25th May 2022) - Melanson, Edward; Depner, Christopher; Wright, Kenneth; Creasy, Seth; Kubicki, Michelle; Zimmerman, Grace
Abstract: Introduction: Chronic diseases are more prevalent among populations with greater daily sedentary time and among populations with insufficient sleep duration. Yet, little is known about the potential links between insufficient sleep and sedentary behavior. Early findings from recent studies show variable and bidirectional associations between sleep duration and sedentary behavior, based on the population studied. The purpose of this investigation was to measure associations between: (1) sleep duration and sedentary time the next day; and (2) sedentary time and sleep duration the same study day/night, during a sleep extension intervention. Methods: Data collection are ongoing. To date, three participants (2 female; aged 24.7±4.04yr; BMI 21.73±2.38kg/m2) with self-reported habitual insufficient sleep (<6.5h per night) completed the study protocol in its entirety. Sedentary behavior (<1.5 METs, in seated or lying posture) and sleep duration were measured via activPALTM and wrist-actigraphy, respectively, at baseline for days 1-13. After baseline, participants completed a sleep extension intervention for study days 15-41, with sedentary behavior and sleep duration measured during study days 28-41. Only study days with full 24h activPAL™ wear time were included in statistical analyses. Associations between sedentary behavior and nightly sleep duration were analyzed by linear mixed-model regression. We focused this preliminary analysis of 3 participants on R2. Results: Sleep duration was significantly increased (p<0.05) during sleep extension (7.6±1.5h) versus baseline (7.0±1.4h). Sedentary behavior was not significantly different (p=0.869) during sleep extension (8.4±1.6h) versus baseline (8.3±2.0h). The association between sleep duration to sedentary time the following day had p=0.683, R2=0.51, and =2.5±6.2h. The association between daily sedentary time to sleep duration the same study day/night had p=0.72, R2=0.12, and =2.3±6.2h. Conclusion: Preliminary findings from 3 participants in this ongoing study suggest that sleep extension is not associated with changes in sedentary behavior. Support (If Any): NIH-UL1TR002535, NIH-K01HL145099, Colorado Clinical Translational Science Institute Pilot (CO-J-20-119), University of Utah Seed Grant-10060570